Antibacterial diaper packaging bag

A antibacterial fiber membrane is prepared by using composite antibacterial agents and electrostatic spinning technology in diapers packaging bags, and polyurethane acrylic was coated to solve the problem of hygiene and mold protection of packaging bags, and achieved long -acting antibacterial and mechanical properties.

CN118814498BActive Publication Date: 2025-01-24FUJIAN MANSHANHONG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411297426.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-24
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing diaper packaging bags are easily touched by human hands during use and storage, resulting in the inability to guarantee hygiene and cleanliness, and may cause mildew to occur due to excessively placed, affecting health.

Method used

Adopting a preparation method of an antibacterial diapers packaging bag, mixing the electrical powder with (3-bromo) trisoplasmium bromide after mixing the ball, adding pupilinol and other ingredients to prepare a composite antibacterial agent, and use ultrasonic treatment through ultrasound treatment The antibacterial fiber membrane is made of static spinning technology, and the effect of polyurethane acrylic was finally fixed with antibacterial effect.

Benefits of technology

The long -acting antibacterial effect of the packaging bag is achieved, the mechanical properties of the packaging bag are enhanced, and the packaging rate and stability of the antibacterial agent are improved, and the hygiene and mold anti -mildew effects of diapers are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an antibacterial diaper packaging bag, and relates to the technical field of packaging bags. The invention uses (3-bromopropyl) trimethylammonium bromide to modify tourmaline, and (3-bromopropyl) trimethylammonium bromide is attached to the surface of the powder through electrostatic adsorption, and under the action of mechanical force, the quaternary ammonium salt is embedded in the interior of the tourmaline, and then dispersed in carvacrol to obtain a composite antibacterial agent, which is then dispersed in a matrix solution of zein, carboxymethyl chitosan, and magnesium chloride. Under the action of ultrasound, zein-loaded antibacterial agent particles are formed, so that the matrix can achieve long-term antibacterial, and an antibacterial film is prepared by electrostatic spinning, and is coated with polyurethane acrylate, and tourmaline and the acrylate therein can be compounded by coupling coordination to improve the mechanical properties of the matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging bags, in particular to an antibacterial diaper packaging bag. Background Art

[0002] Adult incontinence care products (adult diapers, nursing mattresses), maternity care products (maternal sanitary napkins, postpartum care pads, confinement paper, anti-breast pads), infant care products (diapers, pull-up pants, baby mattresses, nursing pads) are becoming more and more diverse, and the classification is becoming more detailed. Various packaging care products can be seen everywhere in major shopping websites and supermarkets. Many sanitary product companies have seen this potential market, increased product structure, and paid more and more attention to product quality. In addition, the design and preparation of packaging bags for care products are also the focus of these companies.

[0003] The common materials of sanitary care product packaging bags on the market include plastic, paper, non-woven fabrics, etc. Plastic packaging bags have unique advantages in water resistance, wear resistance, rigidity and toughness, and are beautifully printed and reasonably priced, so they are the most common packaging materials on the market. Plastic packaging materials are generally high-density polyethylene, which is non-toxic and tasteless, soft and tough, light in weight, chemically stable and will not rust, and is made of brand-new granular material blown film. The packaging bag materials of daily toilet paper are generally thermoplastic resins and chlorinated polypropylene, the packaging bag materials of diapers are generally polyethylene, and the packaging bag materials of sanitary napkins are generally polypropylene, chlorinated polypropylene, thermoplastic resins, thermoplastic polyesters, etc. Then, whether it is the manufacturer of diapers when packaging or when consumers use them, frequent touch by human hands makes the hygiene and cleanliness of the packaging bag and the diapers in it unguaranteed, and the interior may become moldy due to being placed for too long, which is harmful to human health in the long run; therefore, it is particularly necessary to invent an antibacterial diaper packaging bag. Summary of the invention

[0004] The purpose of the present invention is to provide an antibacterial diaper packaging bag to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an antibacterial diaper packaging bag, comprising the following preparation steps:

[0006] (1) Tourmaline powder and deionized water were mixed, ball-milled for 30-60 min, (3-bromopropyl)trimethylammonium bromide was added, and ball-milled for 15-30 min, then filtered, the solid was taken, dried at 50-70 ° C for 18-25 h, carvacrol was added, and stirred at 100-300 rpm for 5-9 h to obtain a composite antibacterial agent;

[0007] (2) The composite antibacterial agent, zein, and 85 wt% ethanol aqueous solution were mixed, and the mixture was slowly added to the composite matrix solution under continuous stirring at 800-1500 rpm, and a 0.2 wt% magnesium chloride aqueous solution was added for ultrasonic treatment, and N,N-dimethylformamide was added for homogenization at 10000 rpm for 3-10 min, followed by centrifugal degassing, and then electrospinning to obtain an antibacterial fiber membrane;

[0008] (3) Heat polyurethane acrylate at 90-120°C at 15-30 g / m 2 The antibacterial diaper packaging bag is obtained by coating the antibacterial diaper on both sides of the antibacterial fiber film and curing the antibacterial diaper.

[0009] Furthermore, the particle size of the tourmaline powder in step (1) is 325 mesh.

[0010] Furthermore, the process parameters of the ball milling in step (1) are as follows: the ball milling medium is mullite microbeads, the ball-to-material ratio is 4:1, and the rotation speed is 700-1200 rpm.

[0011] Furthermore, in step (1), the mass ratio of the tourmaline powder, deionized water, (3-bromopropyl)trimethylammonium bromide and carvacrol is 10:100-200:0.2:10-20.

[0012] Furthermore, the preparation method of the composite matrix solution in step (2) is as follows: carboxymethyl chitosan and deionized water are mixed in a mass ratio of 1.5:100, the temperature is raised to 50-90°C, and the mixture is stirred at 60-120 rpm for 30-60 min. Glycerol in an amount of 0.3-0.9 times the mass of carboxymethyl chitosan is added, and the mixture is stirred for 20-50 min.

[0013] Furthermore, the ultrasonic process parameters in step (2) are: power of 70-120 W and time of 30-60 min.

[0014] Furthermore, in step (2), the centrifugal speed is 5000-7000 rpm and the time is 8-18 min.

[0015] Furthermore, the process parameters of the electrospinning in step (2) are: spinning flow rate 1.5 mL / h, positive voltage 30 kV, negative voltage 2 kV, and receiving distance 22 cm.

[0016] Furthermore, in step (2), the mass ratio of the composite antibacterial agent, zein, 85 wt% ethanol aqueous solution, composite matrix solution, 0.2 wt% magnesium chloride aqueous solution, and N,N-dimethylformamide is 1:2:80~120:300:0.02~0.1:10~40.

[0017] Furthermore, the curing in step (3) is specifically room temperature curing for 30 to 60 minutes.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The invention utilizes (3-bromopropyl)trimethylammonium bromide to modify tourmaline through grinding. (3-bromopropyl)trimethylammonium bromide firstly generates electrostatic action with tourmaline through its charged groups, thereby being adsorbed on the surface of the powder. Then, under the action of mechanical force, the quaternary ammonium salt organic chain in (3-bromopropyl)trimethylammonium bromide is embedded in the silicate crystal layer of the tourmaline, so that the hydrophilic groups on the surface of the original tourmaline are replaced by organic cations, thereby realizing the hydrophobic and lipophilic properties of the tourmaline. Then, the tourmaline is uniformly dispersed in carvacrol, thereby obtaining a composite antibacterial agent. Subsequently, the composite antibacterial agent is dispersed in a matrix solution of zein, carboxymethyl chitosan and magnesium chloride through ultrasound. The large surface tension of the carboxymethyl chitosan solution and the cavitation effect of ultrasound are utilized. When the bubbles are broken, micro jets and shock waves form a cavitation barrier on the matrix. Shear force is exerted to form zein-loaded antimicrobial agent particles with a smaller particle size, which has a certain stabilizing effect on volatile carvacrol, and the positively charged magnesium ions interact with carboxymethyl chitosan through electrostatic attraction, making the structure of the particles in the matrix more compact. In addition, the interaction between the cavitation effects is more conducive to changing the molecular structure of zein, inducing molecular rearrangement, and enhancing the ability to capture antimicrobial agents. At the same time, the encapsulation rate of antimicrobial agents is improved, so that the matrix can achieve long-term antibacterial effect. The antibacterial film is prepared by electrospinning, and is coated with polyurethane and fixed therein, thereby enhancing the long-term antibacterial effect of the matrix and the mechanical properties of the packaging bag. In addition, tourmaline and the acrylate therein can be coupled and coordinated to enhance the density of the polymer chain, thereby improving the mechanical properties of the matrix. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the antibacterial diaper packaging bags prepared in the following examples are as follows:

[0022] Antibacterial property: Take the embodiment and comparative example of the same size and refer to GB / T21510 to test their antibacterial rate, let them stand for 60 days, and test their antibacterial rate again.

[0023] Mechanical properties: The same size of the embodiment and the comparative example were taken according to GB / T1040 to test their tensile strength and elongation at break.

[0024] Example 1; (1) Tourmaline powder with a particle size of 325 mesh and deionized water were mixed and ball-milled for 30 minutes, wherein the ball-milling medium was mullite microbeads, the ball-to-material ratio was 4:1, and the rotation speed was 700 rpm, (3-bromopropyl)trimethylammonium bromide was added, and the ball-milling was continued for 15 minutes, followed by filtration, and the solid was taken and dried at 50° C. for 18 hours, carvacrol was added, and stirred at 100 rpm for 5 hours to obtain a composite antibacterial agent; the mass ratio of the tourmaline powder with a particle size of 325 mesh, deionized water, (3-bromopropyl)trimethylammonium bromide, and carvacrol was 10:100:0.2:10;

[0025] (2) Carboxymethyl chitosan and deionized water were mixed in a mass ratio of 1.5:100, heated to 50°C, stirred at 60 rpm for 30 min, 0.3 times the mass of carboxymethyl chitosan glycerol was added, and stirring was continued for 20 min to obtain a composite matrix solution; the composite antibacterial agent, zein, and 85 wt% ethanol aqueous solution were mixed, and slowly added to the composite matrix solution under continuous stirring at 800 rpm, 0.2 wt% magnesium chloride aqueous solution was added, and ultrasonic treatment was performed at a power of 70 W for 30 min, and N,N-dimethylformamide was added. Amide, homogenized at 10000rpm for 3min, then centrifuged for degassing, the speed is 5000rpm, the time is 8min, then, electrostatic spinning is performed, and the process parameters are: spinning flow rate 1.5mL / h, positive voltage 30kV, negative voltage 2kV, receiving distance 22cm, to obtain an antibacterial fiber membrane; the mass ratio of the composite antibacterial agent, zein, 85wt% ethanol aqueous solution, composite matrix solution, 0.2wt% magnesium chloride aqueous solution, and N,N-dimethylformamide is 1:2:80:300:0.02:10;

[0026] (3) Polyurethane acrylate was heated at 90°C at a temperature of 15 g / m 2 The antibacterial diaper packaging bag is obtained by coating the antibacterial diaper on both sides of the antibacterial fiber film and curing it at room temperature for 30 minutes.

[0027] Example 2; (1) Tourmaline powder with a particle size of 325 mesh and deionized water were mixed and ball-milled for 40 minutes, wherein the ball-milling medium was mullite microbeads, the ball-to-material ratio was 4:1, and the rotation speed was 1000 rpm, (3-bromopropyl)trimethylammonium bromide was added, and the ball-milling was continued for 22 minutes, followed by filtration, and the solid was taken and dried at 60°C for 23 hours, carvacrol was added, and stirred at 200 rpm for 7 hours to obtain a composite antibacterial agent; the mass ratio of the tourmaline powder with a particle size of 325 mesh, deionized water, (3-bromopropyl)trimethylammonium bromide, and carvacrol was 10:150:0.2:15;

[0028] (2) Carboxymethyl chitosan and deionized water were mixed at a mass ratio of 1.5:100, heated to 70°C, stirred at 90 rpm for 45 min, 0.6 times the mass of carboxymethyl chitosan glycerol was added, and stirring was continued for 40 min to obtain a composite matrix solution; the composite antibacterial agent, zein, and 85 wt% ethanol aqueous solution were mixed, and slowly added to the composite matrix solution under continuous stirring at 1100 rpm, 0.2 wt% magnesium chloride aqueous solution was added, and ultrasonic treatment was performed at a power of 90 W for 50 min, and N,N-dimethylformyl was added. Amine, homogenized at 10000rpm for 8min, then centrifuged for degassing, the speed is 6000rpm, the time is 12min, then, electrostatic spinning is performed, and the process parameters are: spinning flow rate 1.5mL / h, positive voltage 30kV, negative voltage 2kV, receiving distance 22cm, to obtain an antibacterial fiber membrane; the mass ratio of the composite antibacterial agent, zein, 85wt% ethanol aqueous solution, composite matrix solution, 0.2wt% magnesium chloride aqueous solution, and N,N-dimethylformamide is 1:2:100:300:0.07:30;

[0029] (3) Polyurethane acrylate was heated at 110°C at 23 g / m 2 The antibacterial diaper packaging bag is obtained by coating the antibacterial diaper on both sides of the antibacterial fiber film and curing it at room temperature for 45 minutes.

[0030] Example 3; (1) Tourmaline powder with a particle size of 325 mesh and deionized water were mixed and ball-milled for 60 minutes, wherein the ball-milling medium was mullite microbeads, the ball-to-material ratio was 4:1, and the rotation speed was 1200 rpm, (3-bromopropyl)trimethylammonium bromide was added, and the ball-milling was continued for 30 minutes, followed by filtration, and the solid was taken and dried at 70°C for 25 hours, carvacrol was added, and stirred at 300 rpm for 9 hours to obtain a composite antibacterial agent; the mass ratio of the tourmaline powder with a particle size of 325 mesh, deionized water, (3-bromopropyl)trimethylammonium bromide, and carvacrol was 10:200:0.2:20;

[0031] (2) Carboxymethyl chitosan and deionized water were mixed at a mass ratio of 1.5:100, heated to 90°C, stirred at 120 rpm for 60 min, 0.9 times the mass of carboxymethyl chitosan glycerol was added, and stirring was continued for 50 min to obtain a composite matrix solution; the composite antibacterial agent, zein, and 85 wt% ethanol aqueous solution were mixed, and slowly added to the composite matrix solution under continuous stirring at 1500 rpm, 0.2 wt% magnesium chloride aqueous solution was added, and ultrasonic treatment was performed at a power of 120 W for 60 min, and N,N-dimethylformamide was added. Amide, homogenized at 10000rpm for 10min, then centrifuged for degassing, the speed is 7000rpm, the time is 18min, then, electrospinning is performed, and the process parameters are: spinning flow rate 1.5mL / h, positive voltage 30kV, negative voltage 2kV, receiving distance 22cm, to obtain an antibacterial fiber membrane; the mass ratio of the composite antibacterial agent, zein, 85wt% ethanol aqueous solution, composite matrix solution, 0.2wt% magnesium chloride aqueous solution, and N,N-dimethylformamide is 1:2:120:300:0.1:40;

[0032] (3) Polyurethane acrylate was heated at 120°C at a temperature of 30 g / m 2 The antibacterial diaper packaging bag is obtained by coating the antibacterial diaper on both sides of the antibacterial fiber film and curing it at room temperature for 60 minutes.

[0033] Comparative Example 1; The difference between Comparative Example 1 and Example 2 is that step (1) is different, and step (1) is changed to: mix tourmaline powder with a particle size of 325 mesh and deionized water, ball mill for 40 minutes, the ball milling medium is mullite microbeads, the ball-to-material ratio is 4:1, the rotation speed is 1000rpm, (3-bromopropyl)trimethylammonium bromide is added, stirred at 500rpm for 2h, then filtered, the solid is taken, dried at 60°C for 23h, carvacrol is added, and stirred at 200rpm for 7h to obtain a composite antibacterial agent; the mass ratio of the tourmaline powder with a particle size of 325 mesh, deionized water, (3-bromopropyl)trimethylammonium bromide, and carvacrol is 10:150:0.2:15; the remaining steps are the same as Example 2.

[0034] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is different, and step (1) is changed to: mixing tourmaline powder with a particle size of 325 mesh and deionized water, ball milling for 40 minutes, wherein the ball milling medium is mullite microbeads, the ball-to-material ratio is 4:1, and the rotation speed is 1000 rpm, followed by filtering, taking the solid, drying at 60° C. for 23 hours, adding carvacrol, and stirring at 200 rpm for 7 hours to obtain a composite antibacterial agent; the mass ratio of the tourmaline powder with a particle size of 325 mesh, deionized water, (3-bromopropyl)trimethylammonium bromide, and carvacrol is 10:150:0.2:15; the remaining steps are the same as in Example 2.

[0035] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (1) is omitted, and step (2) is changed to: carboxymethyl chitosan and deionized water are mixed in a mass ratio of 1.5:100, the temperature is raised to 70°C, and stirred at 90rpm for 45min, glycerol is added in an amount of 0.6 times the mass of carboxymethyl chitosan, and stirring is continued for 40min to obtain a composite matrix solution; carvacrol, zein, and 85wt% ethanol aqueous solution are mixed, and slowly added to the composite matrix solution under continuous stirring at 1100rpm, 0.2wt% magnesium chloride aqueous solution is added, and ultrasonic treatment is performed at a power of 90W for 50min. Add N,N-dimethylformamide, homogenize at 10000rpm for 8min, then centrifuge for degassing at a speed of 6000rpm for 12min, and then perform electrospinning with the following process parameters: spinning flow rate of 1.5mL / h, positive voltage of 30kV, negative voltage of 2kV, and receiving distance of 22cm to obtain an antibacterial fiber membrane; the mass ratio of carvacrol, zein, 85wt% ethanol aqueous solution, composite matrix solution, 0.2wt% magnesium chloride aqueous solution, and N,N-dimethylformamide is 1:2:100:300:0.07:30; the remaining steps are the same as in Example 2.

[0036] Comparative Example 4; The difference between Comparative Example 4 and Example 2 is that step (1) is different. Step (1) is changed to: mix tourmaline powder with a particle size of 325 mesh and deionized water, ball mill for 40 minutes, the ball milling medium is mullite microbeads, the ball-to-material ratio is 4:1, the rotation speed is 1000rpm, (3-bromopropyl)trimethylammonium bromide is added, and the ball milling is continued for 22 minutes, followed by filtration, and the solid is taken and dried at 60°C for 23 hours to obtain an antibacterial agent; the mass ratio of the tourmaline powder with a particle size of 325 mesh, deionized water, and (3-bromopropyl)trimethylammonium bromide is 10:150:0.2; the remaining steps are the same as in Example 2.

[0037] Comparative Example 5; The difference between Comparative Example 5 and Example 2 is that step (2) is different, and step (2) is changed to: carboxymethyl chitosan and deionized water are mixed in a mass ratio of 1.5:100, heated to 70°C, stirred at 90rpm for 45min, 0.6 times the mass of carboxymethyl chitosan glycerol is added, and stirring is continued for 40min to obtain a composite matrix solution; the composite antibacterial agent and 85wt% ethanol aqueous solution are mixed, and slowly added to the composite matrix solution under continuous stirring at 1100rpm, 0.2wt% magnesium chloride aqueous solution is added, and ultrasonic treatment is performed with a power of 90W and a time of 50mi n, add N,N-dimethylformamide, homogenize at 10000rpm for 8min, then centrifuge for degassing at a speed of 6000rpm for 12min, and then perform electrospinning with the following process parameters: spinning flow rate of 1.5mL / h, positive voltage of 30kV, negative voltage of 2kV, and receiving distance of 22cm to obtain an antibacterial fiber membrane; the mass ratio of the composite antibacterial agent, 85wt% ethanol aqueous solution, composite matrix solution, 0.2wt% magnesium chloride aqueous solution, and N,N-dimethylformamide is 1:100:300:0.07:30; the remaining steps are the same as those in Example 2.

[0038] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that step (2) is different. Step (2) is changed to: carboxymethyl chitosan and deionized water are mixed in a mass ratio of 1.5:100, heated to 70°C, stirred at 90rpm for 45min, 0.6 times the mass of carboxymethyl chitosan glycerol is added, and stirring is continued for 40min to obtain a composite matrix solution; the composite antibacterial agent, zein, and 85wt% ethanol aqueous solution are mixed, and slowly added to the composite matrix solution under continuous stirring at 1100rpm, and ultrasonic treatment is performed with a power of 90W and a time of 50mi n, add N,N-dimethylformamide, homogenize at 10000rpm for 8min, then centrifuge for degassing at a speed of 6000rpm for 12min, and then perform electrospinning with the following process parameters: spinning flow rate of 1.5mL / h, positive voltage of 30kV, negative voltage of 2kV, and receiving distance of 22cm to obtain an antibacterial fiber membrane; the mass ratio of the composite antibacterial agent, zein, 85wt% ethanol aqueous solution, composite matrix solution, and N,N-dimethylformamide is 1:2:100:300:30; the remaining steps are the same as those in Example 2.

[0039] Comparative Example 7; The difference between Comparative Example 7 and Example 2 is that step (2) is different, and step (2) is changed to: carboxymethyl chitosan and deionized water are mixed in a mass ratio of 1.5:100, heated to 70°C, stirred at 90rpm for 45min, 0.6 times the mass of carboxymethyl chitosan glycerol is added, and stirring is continued for 40min to obtain a composite matrix solution; the composite antibacterial agent, zein, and 85wt% ethanol aqueous solution are mixed, and slowly added to the composite matrix solution under continuous stirring at 1100rpm, 0.2wt% magnesium chloride aqueous solution is added, stirred at 1500rpm for 100min, and N ,N-dimethylformamide, homogenized at 10000rpm for 8min, then centrifuged for degassing at a speed of 6000rpm for 12min, and then electrospinning was performed with the following process parameters: spinning flow rate 1.5mL / h, positive voltage 30kV, negative voltage 2kV, receiving distance 22cm, to obtain an antibacterial fiber membrane; the mass ratio of the composite antibacterial agent, zein, 85wt% ethanol aqueous solution, composite matrix solution, 0.2wt% magnesium chloride aqueous solution, and N,N-dimethylformamide was 1:2:100:300:0.07:30; the remaining steps were the same as in Example 2.

[0040] Comparative Example 8: The difference between Comparative Example 8 and Example 2 is that step (3) is different, and step (3) is changed to: polyurethane is heated at 110°C at 23g / m 2 Coat on both sides of the antibacterial fiber film and cure at room temperature for 45 minutes to obtain an antibacterial diaper packaging bag; the remaining steps are the same as in Example 2.

[0041] Effect example

[0042] Table 1 below shows the performance analysis results of the antibacterial diaper packaging bags using Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.

[0043] Table 1

[0044]

[0045] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention utilizes (3-bromopropyl)trimethylammonium bromide to grind and modify tourmaline. (3-bromopropyl)trimethylammonium bromide generates electrostatic interaction with tourmaline through its charged groups, thereby adsorbing on the surface of the powder, and under the action of mechanical force, the quaternary ammonium salt organic chain in (3-bromopropyl)trimethylammonium bromide is embedded in the silicate crystal layer of the tourmaline, so that the hydrophilic groups on the surface of the original tourmaline are replaced by organic cations, thereby realizing the hydrophobic and lipophilic properties of the tourmaline, and uniformly dispersed in carvacrol, thereby obtaining a composite antibacterial agent, which is then dispersed in a matrix solution of zein, carboxymethyl chitosan, and magnesium chloride through ultrasound, and the cavitation effect of ultrasound forms a shear force on the matrix, thereby The formation of zein-loaded antimicrobial particles with smaller particle size has a certain stabilizing effect on volatile carvacrol, and the positively charged magnesium ions interact with carboxymethyl chitosan through electrostatic attraction, making the structure of the particles in the matrix more compact. In addition, the interaction between the cavitation effects is more conducive to changing the molecular structure of zein, enhancing the ability to capture antimicrobial agents, and at the same time improving the encapsulation rate of antimicrobial agents, so that the matrix can achieve long-term antibacterial effect. The antibacterial film is prepared by electrospinning and coated with polyurethane acrylate and fixed therein, thereby enhancing the long-term antibacterial effect of the matrix and the mechanical properties of the packaging bag. In addition, tourmaline and the acrylate therein can be coupled and coordinated to enhance the density of the polymer chain, thereby improving the mechanical properties of the matrix.

[0046] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An antibacterial diaper packaging bag, characterized in that: The method comprises the following preparation steps: (1) Tourmaline powder and deionized water are mixed, ball-milled for 30-60 minutes, (3-bromopropyl)trimethylammonium bromide is added, ball-milled for 15-30 minutes, filtered, solids are taken, dried at 50-70°C for 18-25 hours, carvacrol is added, and stirred at 100-300 rpm for 5-9 hours to obtain a composite antibacterial agent; the mass ratio of the tourmaline powder, deionized water, (3-bromopropyl)trimethylammonium bromide, and carvacrol is 10:100-200:0.2:10-20; (2) Carboxymethyl chitosan and deionized water were mixed at a mass ratio of 1.5:100, heated to 50-90°C, stirred at 60-120 rpm for 30-60 min, 0.3-0.9 times the mass of carboxymethyl chitosan glycerol was added, and stirring was continued for 20-50 min to obtain a composite matrix solution; the composite antibacterial agent, zein, and 85 wt% ethanol aqueous solution were mixed, and slowly added to the composite matrix solution under continuous stirring at 800-1500 rpm, and 0.2 wt% magnesium chloride aqueous solution, ultrasonically treated, added N,N-dimethylformamide, homogenized at 10000rpm for 3-10min, then centrifuged for degassing, and then electrospun to obtain an antibacterial fiber membrane; the mass ratio of the composite antibacterial agent, zein, 85wt% ethanol aqueous solution, composite matrix solution, 0.2wt% magnesium chloride aqueous solution, and N,N-dimethylformamide is 1:2:80-120:300:0.02-0.1:10-40; (3) Heat polyurethane acrylate at 90-120°C at 15-30 g / m 2 The antibacterial diaper packaging bag is obtained by coating the antibacterial diaper on both sides of the antibacterial fiber film and curing the antibacterial diaper.

2. The antibacterial diaper packaging bag according to claim 1, characterized in that: The particle size of the tourmaline powder in step (1) is 325 mesh.

3. The antibacterial diaper packaging bag according to claim 1, characterized in that: The process parameters of the ball milling in step (1) are as follows: the ball milling medium is mullite microbeads, the ball-to-material ratio is 4:1, and the rotation speed is 700-1200 rpm.

4. The antibacterial diaper packaging bag according to claim 1, characterized in that: The ultrasonic process parameters of step (2) are: power of 70-120 W and time of 30-60 min.

5. The antibacterial diaper packaging bag according to claim 1, characterized in that: The centrifugal speed in step (2) is 5000-7000 rpm and the time is 8-18 min.

6. The antibacterial diaper packaging bag according to claim 1, characterized in that: The process parameters of the electrospinning in step (2) are as follows: spinning flow rate 1.5 mL / h, positive voltage 30 kV, negative voltage 2 kV, and receiving distance 22 cm.

7. The antibacterial diaper packaging bag according to claim 1, characterized in that: The curing in step (3) is specifically performed at room temperature for 30 to 60 minutes.

Citation Information

Patent Citations

  • Composite powder coating as well as preparation method and application thereof

    CN115717019A

  • Antibacterial preservative film containing composite nanoparticles and preparation method thereof

    CN116675884A